Assessing challenges of implementation halal food certificate among Bumiputera small and medium enterprises - Abu Bakar, Azizi; Saad, Ram Al Jaffri; Basarud-din, Siti Khalilah (2016)
Malaysia's halal certification is important in halal food industry. It’s important to entrepreneurs ensures that every product is produced in according Islamic principal. Therefore, Malaysia needs more entrepreneurs, especially Bumiputera Small and Medium Enterprises (SMEs) to apply for Malaysia’s halal certification. However, halal certification is one of the issues in Malaysia since its compliance to fulfill halal certificate standards among Bumiputera SMEs is still low. The various factors that influence implementation have been suggested in the literature, but this issue from the halal perspective especially Bumiputera SMEs in obtaining halal food certificate is still limited. This study is extensive literature review was utilized to identify and analyze this phenomena. The significance of the study will add the knowledge about the current challenges relating with Bumiputera SMEs in Malaysia in implementation of Malaysian halal certificate.